2017
DOI: 10.1159/000485262
|View full text |Cite
|
Sign up to set email alerts
|

Disease Remission in Children and Adolescents with Intermediate Uveitis: A Survival Analysis

Abstract: Purpose: To report the incidence rate (IR) of remission in pediatric noninfectious intermediate uveitis (IU). Methods: Longitudinal retrospective cohort study, including 19 patients (32 eyes) between 1985 and 2014, followed-up until loss or January 2016. Remission was defined following the Standardization of Uveitis Nomenclature workshop criteria, prolonged remission as a remission spanning 12 months and until the end of follow-up, and relapse as recurrence of inflammatory activity in an eye in remission. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A populationbased study of 48 patients from one county in the United States reported 6/9 or better vision in 85% of patients and 63% of eyes [8]. Long-term follow up in a small case series reported that 25 and 50% of eyes achieved prolonged remission after 5 and 10 years of treatment, respectively [129].…”
Section: Clinical Course and Prognosismentioning
confidence: 99%
“…A populationbased study of 48 patients from one county in the United States reported 6/9 or better vision in 85% of patients and 63% of eyes [8]. Long-term follow up in a small case series reported that 25 and 50% of eyes achieved prolonged remission after 5 and 10 years of treatment, respectively [129].…”
Section: Clinical Course and Prognosismentioning
confidence: 99%